2019
DOI: 10.25259/sni-47-2019
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the myth of outpatient craniotomy for brain tumor in a Sub-Saharan African setting: A case series of two patients in Ibadan, Nigeria

Abstract: Background:The concept of modern neuro-oncology hinges on strategic innovation and refinement of procedures with the intention to enhance safety, optimize extent of tumor resection, and improve not only survival but also the quality of life as well. One of such refinements includes same-day hospital admission, as well as early discharge following brain tumor surgeries. The latter has been further stretched to same-day discharge in particular settings to reduce the risk of nosocomial infections, cut brain tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…OON is not an exception; although it was first described 2 decades ago in Toronto-with an initial protocol success rate of 89% 7 and numerous reports proving its feasibility, safety, and advantages [2][3][4][6][7][8]11 -it is not routinely applied at other centers, with a few exceptions. 5,10,21 For instance, the Toronto OON protocol was implemented at one center in the United Kingdom (UK). 5 Results in the UK, including those for 30 stereotactic biopsies and 11 craniotomies for tumor, showed that the protocol can be successfully adopted in a different healthcare system FIG.…”
Section: Discussion Oon: Current State Of Developmentmentioning
confidence: 99%
“…OON is not an exception; although it was first described 2 decades ago in Toronto-with an initial protocol success rate of 89% 7 and numerous reports proving its feasibility, safety, and advantages [2][3][4][6][7][8]11 -it is not routinely applied at other centers, with a few exceptions. 5,10,21 For instance, the Toronto OON protocol was implemented at one center in the United Kingdom (UK). 5 Results in the UK, including those for 30 stereotactic biopsies and 11 craniotomies for tumor, showed that the protocol can be successfully adopted in a different healthcare system FIG.…”
Section: Discussion Oon: Current State Of Developmentmentioning
confidence: 99%
“…The technological demands of neurophysiological monitoring such as evoked potentials, EMG, and EEG and trained neurophysiologists in addition to certain new anesthetic drugs such as remifentanil and dexmedetomidine are not available in every neurosurgical center especially in developing countries. Many reports described the early experience of awake surgery in localities with limited resources [ 13 – 17 ]. In this study, we describe our experience with awake surgery in our institute.…”
Section: Discussionmentioning
confidence: 99%
“…The Stupp protocol has remained the standard of care for the post-operative care of newly diagnosed GBM (1,25), though with different suggestions of modifications such as the 'super-early' initiation of temozolomide (26). The challenge of the post-operative care of these patients in Nigeria is not predicated on just the high cost of temozolomide, especially when considered in the background of a predominant out-of-pocket healthcare payment, by a majorly poor population with a low minimum wage (27,28), but also on its availability. Thus, only a small percentage of patients can afford or maintain the required chemotherapy cycles.…”
Section: Management and Outcomementioning
confidence: 99%